Populações de macrófagos em músculos esqueléticos de camundongos mdx tratados com ácido eicosapentaenóico - De Carvalho, Samara Camaçarí, 1982- (2012)
Orientadores: Maria Julia Marques, Selma Maria Michelin Matheus